Determination shape and size optimal plot example of measurement for plant species diversity in Mountain Forest - Iwan Hilwan; Yanto Santosa; Siti Nahla (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Information of vegetation structure and composition of terrestrial flora biodiversity can be measured by vegetation analysis method. The method requires sampling plots as a measurement plot capable to describe species in a forest stand. The distribution of a species of diversity, especially plants, is relatively dependent on the type of plant with the condition of the area it occupies. Therefore, an efficient and representative method is needed for the ecosystem in measuring. The objective of the study was to determine the optimal shape and size of sample plots for measuring plant species diversity at stake in TNGHS as well as to assess the most responsive diversity index. The results showed that the shape and size of the optimal sample plot for measuring plant species diversity at stake in TNGHS was a rectangular plot measuring 3.200 m2. The result of the index processing of diversity, it was found that the Margalef Index gave a more responsive diversity value to the change of species number compared with Menhinick, Simpson and ShannonWiener indices. Key words: composition, diversity index, margalef, structure, terrestrial flora.